Evaluation of concentration of thyroid antibodies, antinuclear antibody titers and presence of Borrelia burgdorferi antibodies in patients with vulvar lichen sclerosus treated with photodynamic therapy - Olejek, Anita; Kozak-Darmas, Iwona; Olszak-Wąsik, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2012)
Aim of study : Lichen sclerosus (LS) is a chronic inflammatory disease of skin and mucous membranes. Autoimmune background has been suggested as a potential pathomechanism of LS development. The aim of our study was to evaluate concentration of thyroid antibodies (anti-TSHR, anti-TG and anti-TPO), antinuclear antibody titers and presence of Borrelia burgdorferi antibodies in patients with vulvar lichen sclerosus treated with photodynamic therapy. Materials and methods: Serum samples of 64 patients with diagnosed vulvar LS were taken in order to evaluate presence of Borrelia burgdorferi antibodies, antinuclear antibody titers and concentration of anti- TSHR, anti-TG and anti-TPO antibodies before and after PDT therapy (10 courses). As a topical photosensitizer 5% 5-ALA was applied. For ANA evaluation we used an indirect immunofluorescence test (Euroimmun Mosaic HEp2/monkey liver). In 25 cases we performed the ANA Profile 3 Euroline test to identify particular kinds of ANA. Results: In the case of anti-TSHR, anti-TPO and anti-TG antibodies, results of quantity values were not statistically significant. We noted a statistically significant decrease of ANA titers after PDT therapy. No differences were shown in the identified fluorescent patterns of ANA before and after PDT therapy. IgG and IgM Anti-Borrelia antibodies were found only in 1 and in no subjects, respectively. Conclusions: PDT therapy influences ANA but not anti-TSHR, anti-TPO, anti-TG concentration among patients with diagnosed vulvar LS. In our opinion, Borrelia burgdorferi does not seem to play a significant role in vulvar LS pathogenesis.